Inflation, Credibility, and the Role of the International Monetary Fund - Giannini, Curzio; Cottarelli, Carlo (Washington, D.C. : International Monetary Fund, 1998)
This paper argues that many developing countries may find it difficult to buttress disinflation programs purely through the adoption of traditional credibility-enhancing devices (such as monetary anchors and central bank independence), owing to 'technical problems' (for example, high instability of money demand, increased capital mobility) and an insufficient endowment of credibility in the political institutions. In these cases, borrowing credibility from an outside agency like the International Monetary Fund may be the most effective solution. The paper discusses the different options that would allow the Fund to support programs aimed not at external adjustment-the Fund's traditional role-but at disinflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet